Biologically inspired mobile robot : robot emotion inspired from biological system - 387095 Nor Shahril Che Nazran (Skudai : Universiti Teknologi Malaysia, 2001)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 2001